Financial Legislations in Nigeria: a compendium - Sule, Momodu (Abuja, Nigeria Sumoda Training and Research Centre, 2021)
The book is an assemblage of the following legislations: Bank Employees Etc (Declaration of Assets) Act. 1994; Cheque (Offences) Act, 1977; Advance Fee Fraud and other Fraud Related Offences Act, 2006; Miscellaneous Offences Act, 1983; Foreign Exchange (Monitoring and Miscellaneous Provisions) Act, 1995; Central Bank of Nigeria Act; Insurance Act; Money Laundering Prohibition Act, 2011 as amended and Banks and Other Financial Institutions Act, 2020.
osc 06/02/24
Loans
Keywords: Legislations; Law; Nigeria